The Institution of Lottery: Between Profit and Social Responsibility - Valentina CORNEA; Andreea Elena MATIC (Communications of International Proceedings, 2021)
The general perception of the public on lotteries is that they are actual businesses oriented towards obtaining maximum possible profit. Still, the element of risk which is essential in this activity, does not remove its economic and social character. It should be noted that where lotteries are placed primarily under state control, an important goal is to raise as much money as possible for the state treasury. This goal is sometimes explicitly mentioned in legislation and often in the annual reports of lottery agencies and government studies. The academic and scientific interest in this institution comes from the fact that the lottery is a public service as valuable as any other public service, and its design must meet the standards of efficiency and effectiveness, thus manifesting social responsibility. In this study we aim to analyze the social implications of the Romanian lottery, an institution with a tradition of over 100 years. The first part of the study provides a descriptive picture of the lottery institution, with an emphasis on the design of the institution, the funding model, social responsibility, political decisions on the organization and functioning of the institution. In the second section we will refer to the model of social involvement, by presenting the sponsorship activity. In the final section we will discuss the philanthropic vocation, the problems and the purpose of the lottery institution in the state administrative system and will draw conclusion on the analyzed matter.
Keywords: Public Service; Social Responsibility; Hazard; Philanthropy; Law; Democracy; Freedom of Choice.